Incentives to Reduce Salt Intake Resulting From Women's Experiences: A Qualitative Study. Issue 3 (April 2022) - Soltani, Tahere; Mazloomy Mahmoodabad, Seyed Saeed; Vaezi, Ali Akbar; Nadjarzadeh, Azadeh; Namayandeh, Seyedeh Mahdieh; Soltani, Mohammad Hossein; Fallahzadeh, Hossien
Introduction: Over consumption of salt adversely affects health and is associated with some diseases. Salt over consumption has been reported to be higher in Asian countries including Iran. This research aimed to identify the facilitative factors of reduced salt consumption among 20–65 year-old women to develop effective educational interventions.Methods: This research used qualitative content analysis. We included 42 (31 women aged 20–65 years residing in Hamidia, Yazd and 11 healthcare providers) using Purposeful sampling method. Data were collected through focal group discussions (three groups of 6) and in-depth semi-structured individual interviews with 24 Participants. Data analysis was done using Graneheim and Lundman's approach.Results: Motivators and facilitators were extracted. The former consisted of sub-categories: physical fitness and healthcare, obtaining others' approval, family cooperation and support, internal motivators, contextual motivators and healthcare staff support. Sub-categories of the latter were gaining more information from different instructions, willingness to acquire self-protection skills and nutritional advice. These factors affected to reduce the salt intake among women.Conclusion: In the light of the qualitative results of motivating and facilitating factors, it is essential to enhance internal motivators and increase access to information via different communicative channels in community including schools, medical care providers and public associations. It is also necessary to pave the way for more family and medical staff support, provide appropriate educational and advertising programs, raise women's awareness and change their attitude and behavior with this concern.